Web-based application development for the digitalization of badminton court reservation and scheduling using scrum methodology - Ichwani, Arief; Idris, Mohamad; Afriansyah, Aidil (Institute of Computer Science (IOCS), 2025)
The primary challenge in managing badminton court reservations and scheduling lies in the absence of an integrated system that supports booking, payment flexibility, and efficient schedule management. This study addresses these issues by developing a badminton court reservation information system equipped with user registration, login, court booking, schedule management, payment reporting, and member schedule search features. System evaluation was conducted through a User Acceptance Test (UAT), which confirmed that all core features functioned effectively and met user requirements. To further assess user experience, a Mean Opinion Score (MOS) evaluation involving five respondents and ten questions was carried out, yielding an average score of 3.8 on a four-point scale, categorized as very good. Respondents indicated that the system is easy to use, offers intuitive navigation, has an attractive interface, and provides stable performance while accelerating the booking process. These findings demonstrate that the system is both functionally reliable and well-received by users, thereby contributing to improved administrative efficiency, payment transparency, and overall user convenience.